DOI: 10.11606/t.5.2020.tde-10032020-095906
|View full text |Cite
|
Sign up to set email alerts
|

Análise da decisão de médicos atuantes em cuidados paliativos sobre o uso de antibióticos em pacientes com doenças terminais

Abstract: Crispim DH. Decision-making analysis of palliative care physicians about antibiotic use in terminally ill patients [thesis]. São Paulo: "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
3
0
4
Order By: Relevance
“…It is considered that in EoL patients, even in the presence of a confirmed infection, the use of ABT is not always beneficial, as some authors have previously considered that it is only associated with prolonging the patient's suffering [16]. However, these data disagree with the frequencies in the literature regarding the use of ABT upon suspicion of infection, with several national and international series reflecting high rates of therapy introduction upon the presence of infection (suspected or confirmed), including difficulties in discontinuing it after failure in the first days [10,[17][18]. The discrepancies in these results may be associated with the fact that the questionnaire represents fictitious statements that diverge from real situations, with a component of the doctor-patient relationship, and pressures made by patients or families, which may alter clinicians' decisions at certain times.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that in EoL patients, even in the presence of a confirmed infection, the use of ABT is not always beneficial, as some authors have previously considered that it is only associated with prolonging the patient's suffering [16]. However, these data disagree with the frequencies in the literature regarding the use of ABT upon suspicion of infection, with several national and international series reflecting high rates of therapy introduction upon the presence of infection (suspected or confirmed), including difficulties in discontinuing it after failure in the first days [10,[17][18]. The discrepancies in these results may be associated with the fact that the questionnaire represents fictitious statements that diverge from real situations, with a component of the doctor-patient relationship, and pressures made by patients or families, which may alter clinicians' decisions at certain times.…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide study with 2,400 physicians showed that 16.5% of physicians earn less than 11,000 reais; 19.7% earn between 11,000 and 16,000 reais; 16.3% earn between 16,000 and 21,000 reais; 12% earn between 21, and 27,000 reais; and 17.2% earn more than 27,000 reais 8 . According to the last ANCP survey, PC physicians earn a median value of 94.37 reais per hour worked 9 . The greater number of physicians graduating after the 2000s may reflect the fact that PM is a recent field of practice in Brazil.…”
Section: Sociodemographic Characteristics Of the Surveyed Physiciansmentioning
confidence: 99%
“…Un estudio nacional con 2.400 médicos mostró que el 16,5% de los médicos ganan menos de 11.000 reales; el 19,7% gana entre 11 mil y 16 mil reales; el 16,3% gana entre 16 mil y 21 mil reales; 12% gana entre 21.000 y 27.000 reales y 17,2% gana más de 27.000 reales 8 . Según la última encuesta de la ANCP, un médico que trabaja en CP tiene un valor medio de 94,37 reales por hora trabajada 9 .…”
Section: Continuaciónunclassified